The Malthusian Moment : Global Population Growth and the Birth of American Environmentalism - Robertson, Thomas, 1967- (Book collections on Project MUSE., 2012)
"Although Rachel Carson's Silent Spring (1962) is often cited as the founding text of the U.S. environmental movement, in The Malthusian Moment Thomas Robertson locates the origins of modern American environmentalism in twentieth-century adaptations of Thomas Malthus's concerns about population growth. For many environmentalists, managing population growth became the key to unlocking the most intractable problems facing Americans after World War II--everything from war and the spread of communism overseas to poverty, race riots, and suburban sprawl at home. Weaving together the international and the domestic in creative new ways, The Malthusian Moment charts the explosion of Malthusian thinking in the United States from World War I to Earth Day 1970, then traces the just-as-surprising decline in concern beginning in the mid-1970s. In addition to offering an unconventional look at World War II and the Cold War through a balanced study of the environmental movement's most contentious theory, the book sheds new light on some of the big stories of postwar American life: the rise of consumption, the growth of the federal government, urban and suburban problems, the civil rights and women's movements, the role of scientists in a democracy, new attitudes about sex and sexuality, and the emergence of the "New Right.""--Project Muse